Francis Sargent & Co., Carriages, Sleighs, and Harness; Currier, Philpot, & Co., Sewing Machine Needles - Sampson, Davenport, & Co. (Tufts Archival Research Center, 2005)
Page image of Francis Sargent & Co., Carriages, Sleighs, and Harness; Currier, Philpot, & Co., Sewing Machine Needles from the 1870 Boston City Directory